2011
DOI: 10.1038/ejcn.2011.98
|View full text |Cite
|
Sign up to set email alerts
|

Effect of camel milk on glycemic control and insulin requirement in patients with type 1 diabetes: 2-years randomized controlled trial

Abstract: Background/Objectives: Hypoglycemic effect of camel milk supplementation in experimental rat model and significant reduction in doses of insulin in type 1 diabetic patients have been observed in our previous studies. This long-term study was undertaken to assess the efficacy, safety and acceptability of camel milk as an adjunct to insulin therapy in type 1 diabetics. Subjects/Methods: In this 2-year randomized clinical, parallel design study, 24 type 1 diabetics were enrolled and divided into two groups. Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
117
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(137 citation statements)
references
References 17 publications
6
117
1
2
Order By: Relevance
“…26 The traditional believe in the Middle East is that regular consumption of camel milk helps in prevention and control of diabetes, it has also been reported that camel milk can have such properties. [27][28][29] Such beneficial effects of camel milk might be due to presence of insulin in the milk or some other substances able to modulate glucose level. Our results agree with previous studies that camel milk had a healthy effect by reducing the level of blood glucose that has been elevated by lead acetate exposure.…”
Section: Discussionmentioning
confidence: 99%
“…26 The traditional believe in the Middle East is that regular consumption of camel milk helps in prevention and control of diabetes, it has also been reported that camel milk can have such properties. [27][28][29] Such beneficial effects of camel milk might be due to presence of insulin in the milk or some other substances able to modulate glucose level. Our results agree with previous studies that camel milk had a healthy effect by reducing the level of blood glucose that has been elevated by lead acetate exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, a recent study also proved that camel milk is rich source of insulin (Grover et al, 2014). Furthermore, it is proved that camel milk can be used as an adjunct to insulin therapy as it appears to be safe and efficacious in improving long-term glycemic control and also helps in the reduction of insulin requirement in type 1 diabetic patient (Agrawal et al, 2011). Biochemical studies have revealed the components of camel milk e.g.…”
Section: Anti-diabetic Properties Of Camel Milkmentioning
confidence: 99%
“…Camel milk does seem to contain high levels of insulin or an insulin-like protein which appears to be able to pass through the stomach without being destroyed [67][68][69][70][71][72][73][74][75] and it does not form a coagulum in an acidic environment [76]. Radioimmunoassay tests of camel milk has revealed high concentration of insulin i.e.…”
Section: Camel's Milk To Treat Diabetesmentioning
confidence: 99%